Insights into the interaction between hemorphins and δ-opioid receptor from molecular modeling - Antony, Priya; Baby, Bincy; Vijayan, Ranjit (Frontiers in Molecular Biosciences, 2024)
Hemorphins are short atypical opioid peptide fragments embedded in the β-chain of hemoglobin. They have received considerable attention recently due to their interaction with opioid receptors. The affinity of hemorphins to opioid receptors μ-opioid receptor (MOR), δ-opioid receptor (DOR), and κ-opioid receptor (KOR) has been well established. However, the underlying binding mode and molecular interactions of hemorphins in opioid receptors remain largely unknown. Here, we report the pattern of interaction of camel and other mammalian hemorphins with DOR. Extensive in silico docking and molecular dynamics simulations were employed to identify intermolecular interactions and binding energies were calculated to determine the affinity of these peptides for DOR. Longer forms of hemorphins - hemorphin-7, hemorphin-6, camel hemorphin-7, and camel hemorphin-6 had strong interactions with DOR. However, camel hemorphin-7 and camel hemorphin-6 had high binding affinity towards DOR. Thus, the findings of this study provide molecular insights into how hemorphins, particularly camel hemorphin variants, could be a therapeutic agent for pain regulation, stress management, and analgesia.